Efficiency Analysis Of Commercial Banks And Islamic Commercial Banks : Evidence From Indonesia - Abdullah Haidar; Evania Herindar (The ES Accounting And Finance, 2022)
The purpose of this study is to examine the efficiency of commercial banks (BUK) and Islamic commercial banks (BUS) in Indonesia, which has a total of 19 BUK and 14 BUS. The CRS and VRS models are used in this study to analyse efficiency with data envelopment analysis over a five-year period (2016-2020) using the intermediary approach. According to the study's findings, there are still many BUKs and BUSs that need to improve their efficiency, as well as many efficient BUKs and BUSs. When comparing the two types of banks, the analysis results show that BUK is more efficient than BUS. The output variables, namely the amount of financing and operating income, are the leading cause of BUK and BUS inefficiency in Indonesia. This study also found that the COVID-19 pandemic reduced the efficiency of the BUK while maintaining or slightly increasing the efficiency of the BUS.